FAKTOR FAKTOR YANG MEMPENGARUHI KEPUTUSAN GEN Z DALAM BERTRANSAKSI PADA UMKM MENGGUNAKAN QRIS - Tania Sekar Andina; Marieta Ariani (Bajang Institute, 2026)
This study aims to further examine the influence of financial literacy, financial technology, information security, and perceived ease of use on Gen Z's decisions to transact with MSMEs using QRIS. This study used a quantitative method with a descriptive statistical approach. The population or sample of this study were active students of the Accounting Study Program at Trisakti University, graduating in the 2021-2023 academic year, who made transactions with MSMEs. Purposive sampling was used in the study to attract respondents distributed through a Google form, with a sample size of 150 respondents. Then, the data were analyzed using SPSS (Statistical Package for Social Science) software. The results showed that financial technology, information security, and perceived ease of use had a positive and significant influence on Gen Z's decisions to transact with MSMEs using QRIS. Meanwhile, financial literacy did not have a significant influence on Gen Z's decisions to transact with MSMEs using QRIS.